Estimation of life expectancy in Sistan and Baluchestan province, Iran - Roostaee, Fatemeh; Roostaee, Jhila; Mohammadi, Hamid; Donyavi, Bahram; Keykhaie, Razieh; Sharifi-Rad, Javad; Shahrak, Paridokht; Adrom, Mahdiyeh; Soroush, Fatemeh (International Journal of Research in Medical Sciences, 2017)
Background: Life expectancy deals with the overall level of population health thoroughly considering the effect of mortality. Life expectancy is defined as the expected number of years of life remaining at a given age of people who living in a specific country. This study aimed to estimate life expectancy for the Sistan and Baluchestan province and all its cities based on gender. Methods: This study is a descriptive analytical study. For the analysis of the objectives the required data are mortality information and population data based on age groups and gender. One of the most applicable and most reputed methods in the life table construction is Chaing's methods and was applied this method to estimate life expectancies. Results: Based on the analysis of mortality data, life expectancy at birth for females and males were estimated of 71.5 (This ratio is the percentage of 12 months. 71.5, i.e. 71 years and 6 months) and 68.2 years respectively, and for both sex combined, 69.7 years. These expected years as life expectancy has various values in the rank for the province's cities. In the descending order the values of life expectancies are belong to Khash, Chabahar, Zahedan, Sarbaz, Zabol, Saravan, Nikshahr and Iranshahr cities in the given order. Conclusion:This health indicator has smallest value in Sistan and Baluchestan province in compared to other provinces and whole country as well. To increase life expectancy due to health conditions, economic efficiency and extensive planning by the authorities, planners and policy makers are required.